Design e Estratégia: a identificação dos impactos ambientais nos processos da construção civil, um estudo de caso na Universidade Federal do Maranhão - UFMA - Valporto, Mariana Sousa (2015)
The construction industry is one of major contributor to the environmental degradation, besides, has a significant paper for the economy, generating employment and income. This work identifies the environmental impacts from the construction processes the whole life cycle, for this, it was developed a case study at constructions companies operating in Federal University of Maranhão, in Sao Luis - MA, to collaborate with the reach of the sustainability in the sector. The case study is based at empirical investigation of interpretative character with a descriptive and qualitative analysis by means of ecodesign tools that assess the construction life cycle of each company studied. The results show that decision-making by companies / owners front the environmental practices reflect the lack of planning in the schedule of activities, resulting in waste of material, as well as unpreparedness of the employees, resulting in negative situations related to the requirements for more sustainable actions. Besides the lack of design professionals to assist in the strategic planning of the sector, operation and production processes, applying design management expertise and sustainability.